Institutional Strategies of Identity Constructions and Exclusions: Exploring the State of Rohingya Muslims in Myanmar - Ashwati CK; Rajeesh CS (Otoritas : Jurnal Ilmu Pemerintahan, 2018)
This article elucidates how the widening cultural and ethnic differences are likely to exclude some identities featured by dissensions in terms of their cultural and ethnic origins in the context of Rohingya Muslims in Myanmar. The core intention is to explore the process of exclusion of Rohingyas from a specific national identity. The findings show that Rohingyas access to the national identity can be undermined by the perspectives of the majority, who claims for straightforward sense of national identity. In addition, this work notes down the historical evolution of Rohingya Muslim identity from pre-colonial time to post Independent era with number of skirmishes and scuffles. It is found that through various processes of exclusion, Rohingyas in Myanmar are being compartmentalized and restricted to live in an enclave like situations. Even the squeezed socio-political, cultural and economic lives inside these enclaves are supervised. It makes them socially deserted, culturally discriminated, economically marginalized and politically under-represented. The study employs historical and analytical method to dig out the connection between historical evolution of Rohingyas and their present day status.